Humanizing the economy - Branko Blazevic (UTMS Journal of Economics, 2019)
The arguments that the economy gives us through its great imbalances, crises and wild cycles result in the dehumanization of the society and the human. This paper deals with counter-measures, i.e. with the analysis of the reasons that are in favour of the humanization of the economy, from which follows the humanization of the society and the human. The research is based on numerous secondary sources and the author's reflection that starts from scientific methods of analysis, especially from systems theory and systematic analysis. Solely with the engaged knowledge and understanding of very complex processes and relations in the economy, as well as in other social, humanistic and technical sciences, and with much greater role of science and education in the society (in Croatian society as well), with a devoted engagement of large university potentials in the defence of humanization and integral knowledge, (in Croatia as well) there is a chance for a new large and qualitative step forward. The division of work in science that does not recognize a systemic holistic-ecological science paradigm and does not recognize the scientific methodology of systems theory, results in not having the definition of a subtle boundary, if there is any at all, between social sciences, all of which only blurs the scientific truth even more. Knowledge and understanding in all areas, fields and branches happens right at the universities. This paper pleads for greater involvement of universities, which are most responsible for the scientific truth. Therefore, universities simply have to become the defenders of a humane world.
Keywords: A11; A13; B10; 330; humanization of the economy; macroeconomic goals; economic theories; value paradigms